How is Performance in the Heat Affected by Clothing? (Journal of Fiber Bioengineering and Informatics, 2018)
Adequate heat balance is critical to human performance in the heat. If heat balance cannot bemaintained, the core temperature increases and body water dehydration leads to exhaustion and limitthe performance. Clothing heat transfer properties, thermal insulation and water vapour resistance,modify heat exchange and may indirectly affect performance. Work in protective clothing quicklybecomes exhaustive in impermeable garments, but can be easily completed with much less strain inpermeable garments. Athletes, in particular in sports of endurance type, may produce more than 1000W/m2 in an event lasting several hours. Physical examination of the heat balance of a runner revealsthat a 20% lower water vapour resistance of a covering running suit allows the runner a longer runtime or a higher speed per km before critical physiological strain is reached.
Keywords: performance; heat Stress; core temperature; skin temperature; water vapour resistance